Stronger therapeutic alliance is associated with better quality of life among patients with advanced cancer. Issue 7 (8th March 2021) - Thomas, Teresa; Althouse, Andrew; Sigler, Lauren; Arnold, Robert; Chu, Edward; White, Douglas B.; Rosenzweig, Margaret; Smith, Kenneth; Smith, Thomas J.; Schenker, Yael
Abstract: Objective: Patient–oncologist therapeutic alliance is a foundation of quality cancer care, although there is limited research demonstrating its relationship with patient outcomes. We investigated the relationship between therapeutic alliance and patient quality of life with a secondary goal of determining whether the association varied by patients' baseline level of psychological distress. Methods: Cross‐sectional analysis of baseline data from a randomized clinical trial of 672 patients with advanced cancer participating in a primary palliative care intervention trial. Patients completed baseline self‐reported measures of therapeutic alliance (The Human Connection Scale, range: 16–64), overall quality of life (Functional Assessment of Cancer Therapy—Palliative Care, range: 0–184), and psychological distress (Hospital Anxiety and Depression Scale, range: 0–42). First, we determined the relationship between therapeutic alliance and quality of life using multivariable regression adjusting for confounders. We then examined if psychological distress was an effect modifier in this relationship by adding interaction effects of depression and anxiety symptoms on therapeutic alliance into the regression model. Results: Patients reported high levels of therapeutic alliance (56.4 ± 7.4) and moderate quality of life (130.3 ± 25.5). Stronger therapeutic alliance was associated with better quality of life after adjusting for other confounding factors ( β = 3.7, 95% confidence interval = 2.1, 5.3, p < 0.01). The relationship between therapeutic alliance and quality of life was generally consistent regardless of psychological distress. Conclusions: Collaborative, trusting relationships between patients with advanced cancer and their oncologists are associated with better patient quality of life. Future research should investigate the causal, longitudinal nature of these relationships.